Factors affecting psychosocial well-being and quality of life among women living with HIV/AIDS - U., Shrinivasa Bhat; Cherian, Anish V.; Bhat, Aneesh; Chapman, Helena J.; Lukose, Ammu; Patwardhan, Ninad; Satyanarayana, Veena; Ramakrishna, Jayashree (Journal of Health and Allied Sciences NU, 2015)
Women who are infected with human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) represent a major public health priority due to the disease impact on health, family, and society. Despite the growing number of empirical studies in this area, particularly from developing countries, there are few review articles that explore the psychosocial challenges faced by women living with HIV/AIDS. This clinical review describes prominent factors that influence treatment and quality of life among this target group. Implications and recommendations highlight therapeutic interventions that provide immediate psychosocial and psychophysical support. The review also proposes a conceptual model that may serve as a psychosocial management tool for mental health practitioners in developing countries who counsel women living with HIV/AIDS.
Keywords: HIV/AIDS; Stress; Stigma; Coping; Social support